Prevalence and correlates of the risk of Sexual violence within marriage in Bangladesh - Hadi, Abdullahel (BRAC Research and Evaluation Division (RED), 2019)
Sexual violence against women has never been new in history. What is new is to discover that this kind of act is wrong and has direct impact on women's health. Using data from a nationally representative sample of 500 married women, this research attempts to improve our understanding about the prevalence and determinants of sexual violence within marriage in Bangladesh. The acts of sexual violence during pregnancy, neonatal period and menstruation are examined in rural settings where numerous non-government organisations have intensive credit-based development programmes for the poor. Findings reveal that the probability of a woman to be sexually abused will increase if she is young. illiterate and hails from a landless poor family. Historically, sexual violence within marriage has not been discouraged by the social values, religious beliefs and the legal system of the society. The gendered spousal relationship as well as the risks of sexual abuse has begun to change when women have started to make financial contributions to their families. The paper concludes that involving vulnerable women in productive activities will bring a significant reduction of the risk of sexual violence against them.